Bias Dalam Keputusan Investasi: Mitos Atau Fakta - Johny Budiman; Alex Alex; Angelina Julia Renaldi; Joycelin Joycelin; Shelvi Shelvi (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
This research aims to investigate the financial behavior of investors, including overconfidence bias, herding bias, and self-attribution bias, in their investment decisions. This is a quantitative research study that utilized questionnaire data from 208 respondents, collected through online distribution using Google Forms as the data collection medium. The sampling technique employed in this research is purposive sampling. The results indicate that overconfidence bias, herding bias, and self-attribution bias have a significant positive impact on the investment decisions of investors. Therefore, it is crucial for individuals to acquire investment knowledge early on to avoid biases that can influence investment decisions, ultimately resulting in self-inflicted losses. Additionally, diversifying one's portfolio is important to mitigate future financial losses.